Long-term outcome of patients with steroid-refractory acute severe UC treated with ciclosporin or infliximab. Issue 2 (4th January 2017) - Laharie, D; Bourreille, A; Branche, J; Allez, M; Bouhnik, Y; Filippi, J; Zerbib, F; Savoye, G; Vuitton, L; Moreau, J; Amiot, A; Cosnes, J; et al.
Abstract : Objective: Ciclosporin and infliximab have demonstrated short-term similar efficacy as second-line therapies in patients with acute severe UC (ASUC) refractory to intravenous steroids. The aim of this study was to assess long-term outcome of patients included in a randomised trial comparing ciclosporin and infliximab. Design: Between 2007 and 2010, 115 patients with steroid-refractory ASUC were randomised in 29 European centres to receive ciclosporin or infliximab in association with azathioprine. Patients were followed until death or last news up to January 2015. Colectomy-free survival rates at 1 and 5 years and changes in therapy were estimated through Kaplan-Meier method and compared between initial treatment groups through log-rank test. Results: After a median follow-up of 5.4 years, colectomy-free survival rates (95% CI) at 1 and 5 years were, respectively, 70.9% (59.2% to 82.6%) and 61.5% (48.7% to 74.2%) in patients who received ciclosporin and 69.1% (56.9% to 81.3%) and 65.1% (52.4% to 77.8%) in those who received infliximab (p=0.97). Cumulative incidence of first infliximab use at 1 and 5 years in patients initially treated with ciclosporin was, respectively, 45.7% (32.6% to 57.9%) and 57.1% (43.0% to 69.0%). Only four patients from the infliximab group were subsequently switched to ciclosporin. Three patients died during the follow-up, none directly related to UC or its treatment. Conclusions: In this cohort of patients with steroid-refractory ASUC initially treated by ciclosporin or infliximab, long-term colectomy-free survival was independent from initial treatment. These long-term results further confirm a similar efficacy and good safety profiles of both drugs and do not favour one drug over the other. Trial registration number: EudraCT: 2006-005299-42; ClinicalTrials.gouv number: NCT00542152 ; post-results.